Comparative study of different respiratory muscle training methods: Effects on cardiopulmonary indices and athletic performance in elite short-track speedskaters - Kowalski, T.; Klusiewicz, A.; Rebis, K.; Wilk, A.; Starczewski, M. (Life, 2024)
Respiratory muscle training (RMT) improves endurance performance, balance, and ability to repeat high-intensity exercise bouts, providing a rationale to be applied in short-track speedskating. To establish a preferable RMT method for short-track speedskating, the influence of inspiratory pressure threshold loading (IPTL) and voluntary isocapnic hyperpnoea (VIH) on cardiopulmonary indices and athletic performance was investigated. Sixteen elite short-track speedskaters completed 6 weeks of RMT based on IPTL or VIH. Wingate Anaerobic Tests (WAnTs), cardiopulmonary exercise tests (CPETs), spirometry assessments, and on-ice time trials were performed before and after RMT intervention. Repeated measures ANOVA was used to assess the differences between each method`s influence. No statistically significant (p > 0.05) differences between RMT methods were found in performance during the WAnT, CPET, or specific on-ice time trials. Spirometry measures were similar between both methods. Significant effects were found for the interaction between maximum breathing frequency during CPET (BFmax) and method (p = 0.009), as well as for the interaction between BFMax, method, and sex (p = 0.040). BFmax decreased for IPTL and increased for VIH. The interaction between method and sex revealed that BFmax increased only in males performing VIH. Our findings suggest that IPTL and VIH lead to analogous effects in the study participants, highlighting a negligible practical disparity in the impact of different RMT methods in elite short-track speedskaters.